Aplikasi Quizwhizzer Sebagai Media Pembelajaran Maharah Kitabah Di Ma’had Salafi - Mawarni, Eka; Maksum, M. Syukron; Halifah, Nur; Aminudin (AL-MUTSLA, 2025)
This study aims to describe the development and effectiveness of the QuizWhizzer learning media in improving writing skills (maharah kitabah) in Arabic language learning at Ma'had Salafi. The background of this study departs from the problem of low student interest and participation in Arabic language learning which is still dominated by conventional text-based methods. To address this challenge, this study developed a game-based learning media using the QuizWhizzer application as an interactive and fun digital innovation. This study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments consisted of validation sheets from media experts and material experts, as well as teacher and student response questionnaires. Data were analyzed descriptively quantitatively to assess the level of validity and feasibility of the media. The results showed that the average value of material validity reached 66.7% (quite valid), while the average media feasibility was 82.3% (feasible). The aspect that received the highest score was media usability (85.6%), indicating that QuizWhizzer is easy to use and effective in supporting the learning process. The use of QuizWhizzer has been proven to increase students' motivation, active engagement, and ability to write Arabic texts through interactive, competition-based exercises. Therefore, it can be concluded that QuizWhizzer is a suitable and effective innovative learning tool for improving students' ability to recite Arabic texts. This tool not only enriches teachers' learning strategies but also serves as a relevant tool for integrating digital technology and gamification into Arabic language learning in the Ma'had environment.